Development of the Design Thinking and Instructional Lessons (DTAIL) model: a creative approach for teachers - Elwood, Kristin; Jordan, Michelle E. (Educational technology research and development, 2022)
The educational landscape continues to become increasingly complex, which suggests a need for a teacher-driven creative approach to developing instructional lessons. This article introduces the Design Thinking and Instructional Lessons (DTAIL) model and describes its three-phase development. In Phase I, the Design Thinking literature and the first draft of the model are described. In Phase II and III, two design studies conducted with STEM K-12 public school and community college in-service teachers participating in summer research experience for teachers (RET) programs in the United States are described. In addition, during the second design study, ten teacher-participants were observed as they implemented their lessons and were interviewed concerning how and to what extent they perceived the DTAIL model to resonate with their approach to developing instructional lessons. Revisions to the model were made based on data analysis from those three design phases. Findings suggest that Design Thinking models that facilitate teacher-driven design of instructional lessons might usefully include design stages with an explicit depiction of rotation and recursiveness. In addition, Design Thinking models should also depict (1) iteration, reflection, and revision; (2) a chaotic fluctuating problem–solution space, and (3) circling backward to eventually narrow the problem space toward a satisficed solution. Furthermore, the majority of teacher-participants found the DTAIL model to resonate with their approach to developing instructional lessons.